Tecnologias na educação matemática: o uso do GeoGebra como ferramenta pedagógica no ensino da geometria espacial no Ensino Médio - Araújo, Fernando Silva de (2023)
This paper presents a proposal for teaching spatial geometry using GeoGebra software. Spatial geometry is an area of Mathematics with a wide range of applications, and its teaching is a challenge due to the difficulties in representing geometric solids in planar media, such as whiteboards and books. Thus, the use of Digital Information and Communication Technologies (DICT) demonstrates great potential in facilitating the teaching of spatial geometry and promoting critical and meaningful learning, taking advantage of the growing evolution of these tools, which has driven their integration into the educational scene. In this context, GeoGebra emerges as a powerful tool, having a variety of resources that can be applied in various areas of Mathematics. Aiming to evaluate the use of GeoGebra as a pedagogical tool in the teaching of spatial geometry, this research has a qualitative character, and the methodology used was field research, supported by bibliographic research. To collect the data, a pedagogical intervention was carried out, composed of a diagnosis to verify the students' prior knowledge, a pedagogical workshop, and questionnaires. A high acceptance rate of GeoGebra was observed among the students, who found it easy to use and helpful in visualizing and understanding the elements and measures of a spatial figure. GeoGebra also helped the students to understand a proposed problem situation. Based on the results obtained, it was concluded that GeoGebra is a facilitating tool in the process of learning spatial geometry, promoting dynamic, interactive, and collaborative teaching and contributing to the development of critical thinking, motivation, and student interest.